Development of Smart Content Model-based Augmented Reality to Support Smart Learning - Siti Fatimah; Wawan Setiawan; Enjun Junaeti; Ahmad Syukron Surur (Universitas Pendidikan Indonesia, 2019)
Augmented Reality (AR) is an optical technology that combines virtual objects or worlds into real worlds like in real time and increases user perceptions and interactions with the real world. Information conveyed by virtual objects helps users carry out activities (tasks) in the real world. The convenience offered makes AR technology can be used for various fields, including education, such as the development of materials or learning media. Augmented reality in its development is more comfortable, cheaper, and can be widely implemented in various multimedia needs. This research is a study of the development of multimedia based on augmented reality to produce dynamic learning materials or media in supporting the concept of smart learning. This research provides multimedia models of mathematics for circles, ellipses, parabola, and hyperbole based on augmented reality to create more dynamic learning as smart learning. Multimedia is produced according to operational standards and meets content standards based on media experts, content, and users. Multimedia-based augmented reality math is easy to operate, helps, and increases understanding and increases student motivation.